Characterization of diode pumped solid state laser beam / Wan Aizuddin Wan Razali, Azman Kasim and Syamsyir Akmal Senawi - Wan Razali, Wan Aizuddin; Kasim, Azman; Senawi, Syamsyir Akmal (2011)
Diode Pumped Solid State (DPSS) is an optical pumping for Ti:Sapphire laser. The aim of this project is to diagnose the performance of the DPSS. This laser is operating at continuous wave (cw) mode. The fundamental wavelength of the laser is 1064nm and frequency doubled of KTP crystal to produce a visible green light of 532 nm. The verification of the output is made via the high power laser diode driver. The profile of the beam output was visualized and recorded using Beam Star CCD Profiler. The DPSS laser is started to lase at threshold current of 7 A. The output power of the laser is found to be linearly increased upon the forward current. The slope efficiency was obtained as 0.0576W/A. The maximum output power is obtained as 1.07W corresponding to current of28A. The output beam produced from DPSS laser was in the form of Gaussian Beam at near field.